Robust Receding Horizon Control for Networked and Distributed Nonlinear Systems - Li, Huiping; Shi, Yang.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a comprehensive, easy-to-understand overview of receding-horizon control for nonlinear networks. It presents novel general strategies that can simultaneously handle general nonlinear dynamics, system constraints, and disturbances arising in networked and large-scale systems and which can be widely applied. These receding-horizon-control-based strategies can achieve sub-optimal control performance while ensuring closed-loop stability: a feature attractive to engineers. The authors address the problems of networked and distributed control step-by-step, gradually increasing the level of challenge presented. The book first introduces the state-feedback control problems of nonlinear networked systems and then studies output feedback control problems. For large-scale nonlinear systems, disturbance is considered first, then communication delay separately, and lastly the simultaneous combination of delays and disturbances. Each chapter of this easy-to-follow book notonly proposes and analyzes novel control algorithms and/or strategies, but also rigorously develops provably correct design conditions. It also provides concise, illustrative examples to demonstrate the implementation procedure, making it invaluable both for academic researchers and engineering practitioners.
Introduction and Overview -- RHC of Networked Nonlinear Systems with Two-Channel Packet Dropouts -- Min-Max RHC of Nonlinear NCSs with Delays and Packet Dropouts -- Output Feedback RHC of NCSs with Intermittent Measurements -- Robust Distributed RHC of Constrained Nonlinear Systems -- Distributed RHC of Nonlinear Systems with Communication Delays -- Distributed RHC of Nonlinear Systems: Handling Delays and Disturbances -- Event-Triggered Robust RHC of Continuous-Time Nonlinear Systems.
Keywords: Control engineering; Computer networks .; Telecommunication; Control and Systems Theory; Computer Communication Networks; Communications Engineering, Networks